Longitudinal Analysis of Echocardiographic Abnormalities in Children With Sickle Cell Disease. Issue 7 (October 2017) - Harrington, Jamie K.; Krishnan, Usha; Jin, Zhezhen; Mardy, Christopher; Kobsa, Serge; Lee, Margaret T.
Abstract : Background: Cardiac abnormalities have been described in echocardiograms of children with sickle cell disease (SCD). However, longitudinal studies investigating progression of echocardiographic abnormalities across the pediatric age spectrum in SCD are lacking. Methods: A retrospective longitudinal analysis of 829 echocardiograms from pediatric patients with SCD at steady-state was performed. Left heart parameters included left ventricular end-systolic, end-diastolic diameters, fractional shortening, and mass. Right ventricular pressure was estimated by tricuspid regurgitation gradient. Tricuspid regurgitation gradient ≥25 mm Hg, a z -score ≥2 for LV parameters and ⩽−2 for left ventricular fractional shortening were considered abnormal. Results: Kaplan-Meier analysis revealed that echocardiographic abnormalities were detected by 5 years of age, and the cumulative incidence progressively increased throughout childhood. Age, male gender, HbSS and Sβ θ thalassemia genotype, white blood cell count, platelet count, total bilirubin, admissions for pain crises and acute chest syndrome were positively, whereas hemoglobin was negatively associated with cardiac abnormalities. Conclusion: Cardiac abnormalities began early in childhood and progressively increased with age. Our study highlights the high cumulative incidence of cardiac abnormalities in children with SCD, which could represent a marker of disease severity.